Pengembangan Media Pembelajaran Books Vokal Kids Untuk Meningkatkan Kemampuan Pengenalan Huruf Vokal Pada Anak Usia 5-6 Tahun - Sholihah, Nur Afidatus; Komalasari, Dewi; Reza, Muhammad; Adhe, Kartika Rinakit (Journal of Innovative and Creativity, 2026)
Early childhood literacy fundamental is heavily reliant on the ability to recognize vowel letters. This study aims to determine the feasibility, practicality, and effectiveness of the "Books Vokal Kids" learning media in improving the ability to recognize vowel letters in children aged 5-6 years. The research method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, Disseminate). The research subjects consisted of 10 children in group B3 at TK Muslimat NU 126 Islamiyah. Data collection techniques included observation, questionnaires, and tests, with quantitative and qualitative descriptive data analysis. The results showed that the "Books Vokal Kids" media obtained a feasibility percentage of 88.64% from media experts and 87.5% from material experts, both of which were in the valid category. The practicality test by teachers obtained a score of 75% in the practical category. The effectiveness of the media was proven by the increase in the children's average score from 17.0 (pretest) to 24.2 (posttest). The Wilcoxon test results showed a significance of 0.003 < 0.05, and the N-Gain test was 0.65 (medium category). The conclusion of this study is that "Books Vokal Kids" media is feasible, practical, and effective for improving the vowel letter recognition skills of children aged 5-6 years